Editorial: looking beyond greenness: transdisciplinary approaches to urban green spaces, uses and functions - Vidal, Diogo Guedes (2022)
UGS are complex socioecological systems as they combine both the social and the ecological sphere. Current literature contributed to further elaborate on UGS and their ecosystem services provision (Haines-Young and Potschin, 2018). In spite of those efforts made, ongoing debates still lack a deep meaning about the functions and uses of UGS, which is the most challenging dimension yet to be measured (Fish et al., 2016). Functions and uses of UGS urge for a strong transdisciplinary approach, what could be the reason for the current absence of deeper discussions about this matter. Planning UGS in an era of unpredictability and uncertainty requires a well-built transdisciplinary view to properly address human–nature relations and to integrate scientific knowledge into the decision-making process (Vidal et al., 2021c). Such a lack of knowledge results in the complex phenomena of environmental and social inequalities which are gaining expression specifically within urban areas. Even though it must be acknowledged that other existing contributions within UGS research, embedded within different disciplinary fields, are of great relevance (such as multidimensional research approaches), transdisciplinary perspectives about this matter still lack on subsistence and visibility. So far, previous research has focused on the production of knowledge to improve the quality of the urban environment and to promote the well-being of the population. Notwithstanding, structural inefficiencies and inequalities constantly reproduced in the dense urban environment have been neglected thus far (Jennings et al., 2021). This is closely linked with the unfair distribution of UGS in urban spaces, revealing that disadvantaged communities have lesser physical and symbolic access to qualitative UGS (Dai, 2011; Hoffimann et al., 2017; Vidal et al., 2021a). The phenomenon of “green gentrification” (Curran and Hamilton, 2018) is a further problem which urges for the consideration of environmental injustice enforced by non-equity-oriented policies for urban greening. This, for instance, becomes evident in situations where wealthier migrants experience more benefits compared to those who are socially disadvantaged. Given such shortfalls, the main challenge is to enforce a collective effort to look beyond the greenness, previously addressed by articles integrated within this special issue.